2007
DOI: 10.1242/jeb.004770
|View full text |Cite
|
Sign up to set email alerts
|

Identification and cardiotropic actions of sulfakinin peptides in the American lobster Homarus americanus

Abstract: SUMMARY In arthropods, a group of peptides possessing a–Y(SO3H)GHM/LRFamide carboxy-terminal motif have been collectively termed the sulfakinins. Sulfakinin isoforms have been identified from numerous insect species. In contrast, members of this peptide family have thus far been isolated from just two crustaceans, the penaeid shrimp Penaeus monodon and Litopenaeus vannamei. Here, we report the identification of a cDNA encoding prepro-sulfakinin from the American lobster Homarus americanus. Two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 46 publications
(121 reference statements)
1
39
0
Order By: Relevance
“…Mercier and Russenes, 1992;Wilkens et al, 2005;Cruz-Bermúdez et al, 2006;Cruz-Bermúdez and Marder, 2007;Dickinson et al, 2007;Fort et al, 2007a;Fort et al, 2007b;Christie et al, 2008b;Dickinson et al, 2009). As described earlier, one H. americanus tissue in which CLDH message was detected is the CG, which controls the rhythmic beating of the heart.…”
Section: Homam-cldh Is a Potent Modulator Of Cardiac Outputmentioning
confidence: 69%
See 2 more Smart Citations
“…Mercier and Russenes, 1992;Wilkens et al, 2005;Cruz-Bermúdez et al, 2006;Cruz-Bermúdez and Marder, 2007;Dickinson et al, 2007;Fort et al, 2007a;Fort et al, 2007b;Christie et al, 2008b;Dickinson et al, 2009). As described earlier, one H. americanus tissue in which CLDH message was detected is the CG, which controls the rhythmic beating of the heart.…”
Section: Homam-cldh Is a Potent Modulator Of Cardiac Outputmentioning
confidence: 69%
“…In contrast, the finding of Homam-prepro-CLDH message in the CG was surprising; although the cardiac motor pattern is known to be extensively modulated by peptide hormones (e.g. Mercier and Russenes, 1992;Wilkens et al, 2005;Cruz-Bermúdez et al, 2006;Cruz-Bermúdez and Marder, 2007;Dickinson et al, 2007;Fort et al, 2007a;Fort et al, 2007b;Christie et al, 2008b;Dickinson et al, 2009), no peptides have been identified within the ganglion itself. By dividing the CG into pacemaker neuron-and motor neuron-specific regions, we were able to localize the production of the CLDH transcript to the latter cell type.…”
Section: The Distribution Of Calcitonin-like Diuretic Hormone Mrna Sumentioning
confidence: 92%
See 1 more Smart Citation
“…To date, over two dozen FMRFamide-like peptides have been identified in the nervous system of H. americanus (Trimmer et al, 1987;Stemmler et al, 2007;Dickinson et al, 2007;Ma et al, 2008); amongst these is pQDLDHVFLRFamide (Stemmler et al, 2007;Ma et al, 2008), a member of the Crust-MS subfamily. Immunohistochemistry using antibodies directed against the sequence FMRFamide has long suggested that at least a subset of these peptides is present within the lobster STNS (Fénelon et al, 1998), including within the cell bodies of the PS neurons (Fénelon et al, 1998).…”
Section: Rt-pcr Analysis Suggests That Crust-ms Is Present In the Lobmentioning
confidence: 99%
“…Delivery of myosuppressin to the lobster heart appears to be hormonal H. americanus possesses an extensive collection of FMRFamidelike peptides Dickinson et al, 2007a;Stemmler et al, 2007;Ma et al, 2008), including the myosuppressin isoform studied here Ma et al, 2008). Previous immunohistochemical and/or biochemical/mass spectral mapping of the distribution of this peptide family have shown that these peptides are broadly distributed within the nervous system of the lobster (e.g.…”
Section: Confirmation Of the Structure Of Homarus Americanus Myosupprmentioning
confidence: 99%